Cavin1 Deficiency Causes Disorder of Hepatic Glycogen Metabolism and Neonatal Death by Impacting Fenestrations in Liver Sinusoidal Endothelial Cells. Issue 19 (21st August 2020) - Wei, Zhuang; Lei, Jigang; Shen, Feng; Dai, Yuxiang; Sun, Yan; Liu, Yilian; Dai, Yan; Jian, Zhijie; Wang, Shilong; Chen, Zhengjun; Liao, Kan; Hong, Shangyu
Abstract: It has been reported that Cavin1 deficiency causes lipodystrophy in both humans and mice by affecting lipid metabolism. The ablation of Cavin1 in rodents also causes a significant deviation from Mendelian ratio at weaning in a background‐dependent manner, suggesting the presence of undiscovered functions of Cavin1. In the current study, the results show that Cavin1 deficiency causes neonatal death in C57BL/6J mice by dampening the storage and mobilization of glycogen in the liver, which leads to lethal neonatal hypoglycemia. Further investigation by electron microscopy reveals that Cavin1 deficiency impairs the fenestration in liver sinusoidal endothelial cells (LSECs) and impacts the permeability of endothelial barrier in the liver. Mechanistically, Cavin1 deficiency inhibits the RhoA‐Rho‐associated protein kinase 2‐LIM domain kinase‐Cofilin signaling pathway and suppresses the dynamics of the cytoskeleton, and eventually causes the reduction of fenestrae in LSECs. In addition, the defect of fenestration in LSECs caused by Cavin1 deficiency can be rescued by treatment with the F‐actin depolymerization reagent latrunculin A. In summary, the current study reveals a novel function of Cavin1 on fenestrae formation in LSECs and liver glycogen metabolism, which provide an explanation for the neonatal death of Cavin1 null mice and a potential mechanism for metabolic disorders in patients with Cavin1 mutation. Abstract : Cavin1 deficiency causes severe hypoglycemia, dampens the storage and mobilization of glycogen in mouse liver, and results in neonatal death in C57BL/6J mice. Mechanistically, by inhibiting the dynamics of actin cytoskeleton, Cavin1 deficiency reduces the fenestrae in liver sinusoidal endothelial cells, which impairs bilateral flow between liver glycogen and blood glucose.